ANALISIS PERUBAHAN PENUTUPAN LAHAN MANGROVE DI KABUPATEN SERAM BAGIAN BARAT MALUKU - Debby V Pattimahu (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Analysis of Land Cover Change Mangrove in Western Part of Seram Regency, Maluku. The aim of this study is analyzing land cover change of mangrove in Western Part of Seram Regency Maluku. Results of image Landsat 7 ETM + overlay indicated that mangrove forests area in Western Part of Seram in two years was decreased approximately 174 ha or 7.4%. This affected mangrove land cover changes, because of mangrove exploitation by local communities, expansion of settlements, plantations and clearing The low public education level study sites became the main obstacle in improving their knowledge about the importance of mangrove forestecosystems. Low education level impacted public perception on the lack of mangrove conservationimportance so that they used mangrove forests to fullfill their needs.